"Vi tager lige en snak": Institutionelle fortællinger og samtalens selvfølgelighed i socialpædagogisk praksis - Hansen, Nanna Koch (Tidsskrift for Professionsstudier, 2019)
In the field of social work in the Danish welfare state, establishing dialogue between clients and social workers is typically viewed as key to success. But what is a good dialogue in this context? This article destabilizes common logics and practices which impact social work within the Danish Prison and Probation Service. The article is based on ethnographic fieldwork in two halfway houses and it shows how ideals of natural and unforced dialogue permeate social work. However, at the same time the article shows how such dialogue typically follow a specific template, making staff active co-producers of inmate’s stories.